Drug tolerability: How much ambiguity can be tolerated? A systematic review of the assessment of tolerability in clinical studies - Stanulović, Vid; Hodolic, Marina; Mitsikostas, Dimos D; Papadopoulos, Dimitrios (British journal of clinical pharmacology, 2022)
AIMS: Drug tolerability refers to the degree to which drugs' overt adverse effects can be tolerated by patients. The tolerability profile is of comparative importance to its efficacy and safety, as it largely determines adherence to treatment and ultimately treatment success or failure. However, the term is frequently used imprecisely, and it is unclear if tolerability is limited to subjective patient-reported symptoms or also covers certain objective signs and findings. The aim of this systematic review was to assess how clinical studies define, evaluate and present drug tolerability. METHODS: The study consisted of a systematic review of clinical studies in PubMed® reporting the term "tolerability". RESULTS: Eighty clinical studies were screened and 56 studies reporting drug tolerability were retained. None of the retained studies defined events encompassed by the term tolerability by making a distinction between safety and tolerability. Twenty-five studies claimed to evaluate tolerability, but none of them described how to evaluate tolerability from the patient perspective. Most studies (54 out of 56) concluded that the treatment was well tolerated, apparently implying favourable safety. However, none of them actually presented tolerability in terms of a contrast between safety and tolerability. CONCLUSIONS: Tolerability is used frequently, albeit incorrectly, to refer to a drug's favourable safety profile. Focused evaluation of drug tolerability (i.e., the patient perspective of adverse drug reactions) should become routine. Presentation in regulatory documents, such as risk management plan summaries, product information and patient leaflets should be a continuation of the process of patient-centred healthcare.
Keywords: Drug-Related Side Effects and Adverse Reactions; Humans; výsledek terapie; lidé; nežádoucí účinky léčiv; Treatment Outcome